2007
DOI: 10.1063/1.2813625
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties and percolation in carbon nanotube-polymer composites

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(160 citation statements)
references
References 20 publications
3
156
1
Order By: Relevance
“…electrical conductivity as compared to those prepared using other techniques. The electrical and thermal properties of carbon nanomaterial/polymer composites are widely described using percolation theory, though the term "thermal percolation" is still a subject of debate [74,75]. In the case of electrical percolation, at very low filler loadings, the conductivities remain very close to the insulating pure polymers since the fillers are in a random arrangement.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…electrical conductivity as compared to those prepared using other techniques. The electrical and thermal properties of carbon nanomaterial/polymer composites are widely described using percolation theory, though the term "thermal percolation" is still a subject of debate [74,75]. In the case of electrical percolation, at very low filler loadings, the conductivities remain very close to the insulating pure polymers since the fillers are in a random arrangement.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…12,13 CNTs have a unique one-dimensional structure that enables the composites filled with CNTs to have low percolation threshold concentrations. 14,15 Due to these characteristics, composites filled with CNTs show the enhancement of thermal conductivity even at low concentrations. 16,17 Fan et al reported a significant effect of the alignment of CNTs on thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a small difference in operating temperature in the order of 10~15 o C can result in a two-fold reduction in the life time of the electronic devices [24]. CNT has the one-dimensional unique structure which enables the composites filled with CNT to have low percolation threshold concentrations [25,26]. By using this characteristics, CNT incorporated composites show the thermal conductivity enhancement at low concentrations [27,28].…”
Section: Thermal Conductivity Of Cnt-polymer Compositesmentioning
confidence: 99%